The Haves and the Have Nots: Civic Technologies and the Pathways to Go vernment Responsiveness - Mellon, Jonathan; Peixoto, Tiago C; Sjoberg, Fredrik M (World Bank, 2022)
“Civic tech” broadly refers to the use of digital technologies to supp ort a range of citizen engagement processes. From allowing individuals to report problems to local government to enabling the crowdsourcing of national legislation, civic tech aims to promote better policies an d services – while contributing to more inclusive democratic instituti ons. But could civic tech affect public issues in a way that benefits some and excludes others? Over the decades, the question of who partic ipates in and who is excluded from participation mediated by technolog y has been the focus of both civic tech critics and proponents. The la tter tend to argue that, by enabling citizens to participate without c onstraints of time and distance, civic tech facilitates the participat ion of those who usually abstain from engaging with public issues, lea ding to more inclusive processes. Critics argue that, given the existi ng digital divide, unequal access to technology will tend to empower t he already empowered, further deepening societal differences. Yet both critics and proponents do tend to share an intuitive assumption: the socio-economic profile of who participates is the primary determinant of who benefits from digitally mediated civic participation. For insta nce, if more men participate, outcomes will favor male preferences, an d if more young people participate, outcomes will be more aligned with the concerns of the youth. In a new paper, we show that the link betw een the demographics of those participating through digital channels, and the beneficiaries of the participation process, is not necessarily as straightforward as commonly assumed. We review four civic tech cas es where data allow us to trace the full participatory chain through: the initial digital divide the participant’s demographics the demands made through the process the policy outcomes We examine online voting in the Brazilian state of Rio Grande do Sul’s participatory budgeting process, the local problem reporting platform Fix My Street (FMS) in t he United Kingdom, Iceland’s online crowdsourced constitution process, and the global petitioning platform Change.org. Counterintuitive find ings Change.org has been used by nearly half a billion people around t he globe. Using a dataset of 3.9 million signers of online petitions i n 132 countries, we examine the number of successful petitions and ass ess whether petitions created by women have more success than those su bmitted by men. Our analysis shows that, even if women create fewer on line petitions than men, their petitions are more likely to be success ful. All else equal, when online petitions have an impact on governmen t policy, the agenda being implemented is much closer to the issues wo men choose to focus on. In Rio Grande do Sul’s digital participatory b udgeting (PB), we show that despite important demographic differences between online and offline voters, these inequalities do not affect wh ich types of projects are selected for funding – a consequence of PB’s unique institutional design, which favors redistributive effects. In fact, of all the cases analyzed, none reflect the standard assumption that inequalities in who participates translate directly into inequali ties in who benefits from the policy outcomes. Our results suggest tha t the socio-economic profile of participants predicts only in part who benefits from civic tech. Just as important to policy outcomes is how the platform translates civic participation into policy demands, and how the government responds to those demands. While civic tech practit ioners pay a lot of attention to design from a technological perspecti ve, our findings highlight the importance of considering how civic tec h platforms function as political institutions that encourage certain types of behavior while discouraging others. Civic tech, it seems, is not inherently good nor bad for democratic institutions. Instead, its effect is a combination of who participates on digital platforms and t he choices of platform designers and governments.